Leveraging Generative AI for Strategic Design Visualization and Innovation in Early-Stage of Product Development Among Students - Muhammad Jameel, Mohamed Kamil; Johari, Abdullah (Strategic Design Research Journal (SDRJ), 2024)
Generative models in Artificial Intelligence (AI), such as Stable Diffusion and ChatGPT, are increasingly employed across diverse fields, including product design, for tasks like shape recognition and design creation. The convergence of physical and digital realms is emerging as a prominent trend in art and design. This trend underscores generative models' ability to bridge offline and online environments in creative endeavours. This article aims to investigate the potential of integrating generative image AI into a strategic design visualization process among product design students. Using image-based research analysis and semi-structured interviews, this study involved five product design students as respondents. The findings highlight that integrating generative AI tools, particularly the Copilot Bing Image Creator, significantly enhances product design education. It improves students' creativity and streamlines the design process. This integration not only closes the gap between creative concepts and practical applications but also offers a robust framework for evaluating AI-generated content. Ultimately, it enhances the quality, practicality, and comprehension of design processes among students. This study underscores the transformative potential of generative AI tools in strategic design process, showcasing their effectiveness in fostering creativity, efficiency, and design quality.